Waist circumference and waist‐to‐height ratio in 7‐year‐old children—WHO Childhood Obesity Surveillance Initiative. (17th August 2021) - Taxová Braunerová, Radka; Kunešová, Marie; Heinen, Mirjam M.; Rutter, Harry; Hassapidou, Maria; Duleva, Vesselka; Pudule, Iveta; Petrauskienė, Aušra; Sjöberg, Agneta; Lissner, Lauren; Spiroski, Igor; Gutiérrez‐González, Enrique; et al.
Summary: Childhood obesity is a serious global health problem. Waist circumference (WC) and waist‐to‐height ratio (WHtR) reflect body fat distribution in children. The objectives of this study were to assess WC and WHtR in 7‐year‐old children and to determine body mass index (BMI), WC, and WHtR differences in children from 10 selected countries across Europe (Bulgaria, Czechia, Greece, Ireland, Latvia, Lithuania, North Macedonia, Norway, Spain, and Sweden) participating in the World Health Organization (WHO) Europe Childhood Obesity Surveillance Initiative (COSI). The 50th and 90th percentile of WC (according to COSI and "Identification and prevention of Dietary‐ and lifestyle‐induced health EFfects In Children and infantS" (IDEFICS) cutoff values) and WHtR above 0.5 were used as measures of abdominal obesity in a unique sample of 38, 975 children aged 7.00–7.99 years. Southern European countries, including Greece and Spain, showed significantly higher BMI, WC, and WHtRin both genders ( p < 0.0001) than Eastern and Northern Europe. The highest values for WC were observed in Greece (60.8 ± 7.36 cm boys; 60.3 ± 7.48 cm girls), North Macedonia (60.4 ± 7.91 cm boys; 59.0 ± 8.01 cm girls), and Spain (59.7 ± 6.96 cm boys; 58.9 ± 6.77 cm girls). WC and WHtRin may add an information about the occurrence of central obesity in children.